Competitive Advantages of Small Medium Industry on the Islands in Indonesian Context - Kurniawan, Muslim El Hakim; Yudoko, Gatot; Basri, Mursyid Hasan (International Research Journal of Business Studies, 2018)
Indonesian Law No.3/2014 regarding Industry requires both Central and Local Governments to realize the competitiveness of small and medium industries. However, the fact that the condition of each region is not similar becomes a main problem. It is because Indonesia is an archipelagic country. The competitiveness index of Asia Competitiveness Institute 2015 indicates that islands provinces, such as Kepulauan Bangka Belitung, Nusa Tenggara Barat, Nusa Tenggara Timur, Sulawesi Utara, Maluku, Maluku Utara, Sulawesi Tenggara, need specific development strategies. They cannot be equated with the mainlands, such as Java and Sumatera, because their competitiveness rank is very low. A review of literature on the competitiveness of islands entrepreneurs shows that from the 4 (four) schools of thought in competitive advantage, only few researchers have pertained on the knowledge based on the schools of thought. Therefore, this could be a future research opportunity.